Get outta my face! : how to reach angry, unmotivated teens with biblical counsel - Horne, Rick. (Wapwollopen, Pa. : Shepherd Press, 2009)
Here's a fact. Angry, unmotivated, and disinterested teens, whether Christian or not, are confused, insecure, and often blind to everything except what they want right now. Their desires and actions have been corrupted and polluted by sin. That's why they have a problem. Here's another fact. Angry, unmotivated, and disinterested teens, whether Christian or not, are made in the image of God. This means that beneath their corrupted desires and actions the image of God remains. That's the key to solving their problem. Far from dismissing or sugar-coating sin, this approach opens wide the door to evangelizing the unsaved teen and to helping the Christian teen grow in holiness and wisdom. This book will teach you how to build a bridge to young adults on the basis of the ways in which their desires and actions reflect the image of God and the blessing of common grace. - Publisher.
Part I: What you must understand to connect with your teen: There is good reason for hope -- Understanding your teen biblically -- Wise wants: a point of contact -- Your stance: determine to glorify God -- Your stance: remember the log in your own eye -- Part II: What you must do to help your teen: Listen big: build a bridge to your teen -- Clarify narrow: expose the realities of your teen's experience -- Look wide: discover your teen's solutions --Plan small: support changes your teen wants -- Part III: How to make the changes stick: Keep the conversation going in the right direction -- Point your teen to the cross.
Includes bibliographical references (page 172) and scripture index.
Keywords: Parent and teenager; Parenting; Patent and teenager -- Religious aspects; Parenting -- Religious aspects; Teenagers -- Family relationships; Teenagers -- Religious life; Teenagers -- Conduct of life